South African study of blast phase chronic myeloid leukaemia: A poor prognostic outlook - Katherine E. Hodkinson; Nikki Bouwer; Jenifer Vaughan (AOSIS, 2022)
Background: Chronic myeloid leukaemia (CML) is a haematological malignancy characterised by the translocation t(9;22)(q34;q11.2), resulting in a constitutively active tyrosine kinase. Globally, overall survival of blast crisis phase (BC) CML is one year. Newer tyrosine kinase inhibitors and allogeneic stem cell transplantation offer remission; however, refractory and relapsed disease remain the biggest challenges. Objective: In South Africa, literature is lacking on BC-CML. This study aimed to determine the disease characteristics and overall survival in South Africa. Methods: This retrospective, laboratory-based study reviewed all new BC-CML diagnoses via flow cytometry at Charlotte Maxeke Johannesburg Academic Hospital in Johannesburg, South Africa, between April 2016 and October 2019. BC-CML was defined as the presence of 20% blasts with a CML history or the BCR-ABL1 fusion gene (p210/p190) in the appropriate clinical or pathological context. Survival outcomes were inferred from clinical and laboratory data. Results: Twenty-two new cases of BC-CML were diagnosed (median age: 34 years). There were 20 (91%) cases with the fusion transcripts p210 and two (9%) cases with p190 BCRABL1. For blast lineage, 14 cases were myeloid (63.6%), six were lymphoid (27.3%), and two were ambiguous (9.1%). There was a 72.7% mortality (16 cases); sepsis, refractory and relapsed disease were the major causes. Patients who achieved remission had lower blast percentages, simple karyotypes, and a trend towards higher white cell and platelet counts at presentation. Conclusion: Optimised management of early-stage CML, prevention and aggressive management of sepsis, with advocation for newer therapies are needed to improve the overall survival of BC-CML in South Africa.